2011
DOI: 10.2337/db11-0851
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cellular Defect in Diabetes

Abstract: OBJECTIVESkeletal muscle myopathy is a common diabetes complication. One possible cause of myopathy is myocyte failure to repair contraction-generated plasma membrane injuries. Here, we test the hypothesis that diabetes induces a repair defect in skeletal muscle myocytes.RESEARCH DESIGN AND METHODSMyocytes in intact muscle from type 1 (INS2Akita+/−) and type 2 (db/db) diabetic mice were injured with a laser and dye uptake imaged confocally to test repair efficiency. Membrane repair defects were also assessed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 48 publications
4
69
0
Order By: Relevance
“…2 ). Because membrane repair occurs rapidly in the presence of calcium [e.g., ( 20,21 ) and see below], this result indicates that upon membrane repair, PLD activity returned to basal levels, suggesting a possible role for this enzyme in the repair process.…”
Section: Activation Of Pld By Cell Wounding Induced Upon Cell Liftingmentioning
confidence: 72%
See 2 more Smart Citations
“…2 ). Because membrane repair occurs rapidly in the presence of calcium [e.g., ( 20,21 ) and see below], this result indicates that upon membrane repair, PLD activity returned to basal levels, suggesting a possible role for this enzyme in the repair process.…”
Section: Activation Of Pld By Cell Wounding Induced Upon Cell Liftingmentioning
confidence: 72%
“…A laser was used to disrupt cell membranes in the presence of a lipid-soluble fl uorescent dye. This dye enters the cell and binds to membrane-delimited cell organelles such that the fl uorescence intensity of the cell continues to increase until the membrane disruption is repaired, thereby halting dye entry ( 20,21 ). Because membrane repair requires calcium with 1,25(OH) 2 D 3 for 24 h before monitoring PLD activation in lifted cells as in Fig.…”
Section: Effect Of Pld Inhibition On Wound Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Defect in the muscle cell's ability to repair has been shown to result in muscular dystrophy, [3][4][5][6] where poor repair of injured muscle cell membrane leads to cell death and tissue inflammation. Poor plasma membrane repair (PMR) is also associated with NiemannPick type A, 7 diabetes, 8 and ChediakHigashi 9 syndrome and therapies targeting PMR have been shown to be effective in treating muscle and lung injuries. [10][11][12] While much of the focus has been on disease resulting from poor PMR, we have recently identified that improved PMR is an important contributor for cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Still, many cells experience plasma membrane ruptures on a recurring basis that they need to cope with to maintain cell and tissue integrity. Disease results from defect in the repair system and is associated with cancer [1] , diabetes [2] , Chediak-Higashi [3] syndrome and muscular dystrophies [4] .…”
Section: Introductionmentioning
confidence: 99%